2015
DOI: 10.1016/j.energy.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of micromixing on performance of a membrane-based absorber

Abstract: a b s t r a c tIn this study, microstructures are employed to manipulate thermohydraulic characteristics of the lithium bromide (LiBr) solution flow in a membrane-based absorber in order to enhance the absorption rate. In a membrane-based absorber, the liquid absorbent is constrained between a solid wall and a highly permeable membrane, thus facilitating manipulation of the flow properties. Recent numerical studies have shown that transport mode in a laminar flow can be changed from diffusive to advective via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 32 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…According to the authors, the reduced size of the membrane absorbers could help develop new absorption cooling systems for small scale applications. Isfahani et al [ 111 ] studied the performance of a membrane absorber with microstructures on the solution flow channel to promote vortex generation and to improve the mass transfer process. The microchannels were 0.5 mm deep, 1 mm wide, and 195 mm long, while the microstructures were 0.2 mm deep and were in a 30° herringbone arrangement.…”
Section: Membrane-based Absorbersmentioning
confidence: 99%
“…According to the authors, the reduced size of the membrane absorbers could help develop new absorption cooling systems for small scale applications. Isfahani et al [ 111 ] studied the performance of a membrane absorber with microstructures on the solution flow channel to promote vortex generation and to improve the mass transfer process. The microchannels were 0.5 mm deep, 1 mm wide, and 195 mm long, while the microstructures were 0.2 mm deep and were in a 30° herringbone arrangement.…”
Section: Membrane-based Absorbersmentioning
confidence: 99%
“…It was also higher than the value reported by Ali and Shwerdt [1] in their plate absorber. Later, Isfahani et al [13] employed micro protrusions on the solution channel wall to enhance the absorption rate.…”
Section: Introductionmentioning
confidence: 99%
“…This challenge can be addressed by implementing a thermal barrier like a membrane [9]- [13], which allows mass transfer of vapor but impedes heat transfer from the interface to the air side. Membrane technology can also enable absorption enhancement techniques like micromixing (demonstrated numerically by Bigham et al [14] and experimentally by Nasr Isfahani et al [15]) or can be combined with a finned structure as demonstrated in Mortazavi et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…The unknowns are α, T interface , and . Note that T interface appears as an argument in an equilibrium EOS for vapor pressure in Equation (15). Since this EOS does not have a simple analytical form, a solution of this system of three equations must be pursued using a numerical solver.…”
mentioning
confidence: 99%
See 1 more Smart Citation